Expanded substrate screenings of human and Drosophila type 10 17beta-hydroxysteroid dehydrogenases (HSDs) reveal multiple specificities in bile acid and steroid hormone metabolism: characterization of multifunctional 3alpha/7alpha/7beta/17beta/20beta/21-HSD. - Shafqat, N; Marschall, H; Filling, C; Nordling, E; Wu, X; Björk, L; Thyberg, J; Mårtensson, E; Salim, S; Jörnvall, H; Oppermann, U (2003)
17beta-hydroxysteroid dehydrogenases (17beta-HSDs) catalyse the conversion of 17beta-OH (-hydroxy)/17-oxo groups of steroids, and are essential in mammalian hormone physiology. At present, eleven 17beta-HSD isoforms have been defined in mammals, with different tissue-expression and substrate-conversion patterns. We analysed 17beta-HSD type 10 (17beta-HSD10) from humans and Drosophila, the latter known to be essential in development. In addition to the known hydroxyacyl-CoA dehydrogenase, and 3alpha-OH and 17beta-OH activities with sex steroids, we here demonstrate novel activities of 17beta-HSD10. Both species variants oxidize the 20beta-OH and 21-OH groups in C21 steroids, and act as 7beta-OH dehydrogenases of ursodeoxycholic or isoursodeoxycholic acid (also known as 7beta-hydroxylithocholic acid or 7beta-hydroxyisolithocholic acid respectively). Additionally, the human orthologue oxidizes the 7alpha-OH of chenodeoxycholic acid (5beta-cholanic acid, 3alpha,7alpha-diol) and cholic acid (5beta-cholanic acid). These novel substrate specificities are explained by homology models based on the orthologous rat crystal structure, showing a wide hydrophobic cleft, capable of accommodating steroids in different orientations. These properties suggest that the human enzyme is involved in glucocorticoid and gestagen catabolism, and participates in bile acid isomerization. Confocal microscopy and electron microscopy studies reveal that the human form is localized to mitochondria, whereas Drosophila 17beta-HSD10 shows a cytosolic localization pattern, possibly due to an N-terminal sequence difference that in human 17beta-HSD10 constitutes a mitochondrial targeting signal, extending into the Rossmann-fold motif.